2006
DOI: 10.1152/ajpregu.00261.2006
|View full text |Cite
|
Sign up to set email alerts
|

Descending vasa recta endothelium is an electrical syncytium

Abstract: We examined gap junction coupling of descending vasa recta (DVR). DVR endothelial cells or pericytes were depolarized to record the associated capacitance transients. Virtually all endothelia and some pericytes exhibited prolonged transients lasting 10 -30 ms. Carbenoxolone (100 M) and 18␤-glycyrrhetinic acid (18␤GRA; 100 M) markedly shortened the endothelial transients. Carbenoxolone and heptanol (2 mM) reduced the pericyte capacitance transients when they were prolonged. Lucifer yellow (LY; 2 mM) was dialyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 59 publications
(93 reference statements)
3
26
0
Order By: Relevance
“…In addition to Ba 2ϩ , the application of extracellular Cs ϩ (10, 100, and 1,000 M) also inhibited inwardly rectifying currents in a dose-dependent fashion (10 M, 53 Ϯ 3.7%; 100 M, 57.6 Ϯ 9.0%; 1,000 M, 76.1 Ϯ 6.9% at Ϫ140 mV, respectively), and the pattern of Cs ϩ blockage was also similar to that of Cs ϩ blockage reported in other cells (Fig. 4, A and B) (7,51). Our data showed that inward rectifying K ϩ currents are dose-dependently inhibited by Kir blockers.…”
Section: Characterization Of Human Umbilical Cord Blood-derivedsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to Ba 2ϩ , the application of extracellular Cs ϩ (10, 100, and 1,000 M) also inhibited inwardly rectifying currents in a dose-dependent fashion (10 M, 53 Ϯ 3.7%; 100 M, 57.6 Ϯ 9.0%; 1,000 M, 76.1 Ϯ 6.9% at Ϫ140 mV, respectively), and the pattern of Cs ϩ blockage was also similar to that of Cs ϩ blockage reported in other cells (Fig. 4, A and B) (7,51). Our data showed that inward rectifying K ϩ currents are dose-dependently inhibited by Kir blockers.…”
Section: Characterization Of Human Umbilical Cord Blood-derivedsupporting
confidence: 82%
“…The application of extracellular Ba 2ϩ (1, 10, and 100 M) inhibited inwardly rectifying currents in a dose-dependent fashion (1 M, 26.2 Ϯ 4.1%; 10 M, 88.5 Ϯ 4%; 100 M, 91.2 Ϯ 1.4% at Ϫ140 mV, respectively) and the pattern of Ba 2ϩ blockage was similar to that of Ba 2ϩ blockage reported in other cells (Fig. 3, A and B) (7,51). In addition to Ba 2ϩ , the application of extracellular Cs ϩ (10, 100, and 1,000 M) also inhibited inwardly rectifying currents in a dose-dependent fashion (10 M, 53 Ϯ 3.7%; 100 M, 57.6 Ϯ 9.0%; 1,000 M, 76.1 Ϯ 6.9% at Ϫ140 mV, respectively), and the pattern of Cs ϩ blockage was also similar to that of Cs ϩ blockage reported in other cells (Fig.…”
Section: Characterization Of Human Umbilical Cord Blood-derivedsupporting
confidence: 80%
“…3D). We showed that the DVR endothelium is an electrical syncytium and that connexins are expressed by both pericytes and endothelial cells (46). Figure 3 shows that asynchronous [Ca 2ϩ ] CYT changes occur between individual pericytes and between pericytes and adjacent endothelium despite putative interendothelial and myoendothelial coupling.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, endothelial depolarization is transmitted to adjacent endothelial cells. Spread of electrogenic signals can occur on a time scale that is less than a millisecond (53,57,58). The physiological role of transmission through cells of vessel walls has been frequently reviewed (5,14,22,46).…”
mentioning
confidence: 99%